2019
DOI: 10.1016/j.ijid.2019.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance in Cambodia: a review

Abstract: Objectives: Following the launch of the Global Antimicrobial Resistance Surveillance System (GLASS), antimicrobial resistance (AMR) rates in many countries remain poorly described. This review provides an overview of published AMR data from Cambodia in the context of recently initiated national human and food-animal surveillance. Methods: PubMed and the Cochrane Database of Systematic Reviews were searched for articles published from 2000 to 2018, which reported antimicrobial susceptibility testing (AST) data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 59 publications
2
21
0
Order By: Relevance
“…Besides, there is high variability among the criteria relevant to methodology and interpretation. This is consonant with the data depicted elsewhere in recent similar reviews [77,78,86,90]. There are some calls to adopt standardized AMR data presented in published papers, wishing to make the ndings interpretable and comparable from the perspective of scarce homogeneity [111].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Besides, there is high variability among the criteria relevant to methodology and interpretation. This is consonant with the data depicted elsewhere in recent similar reviews [77,78,86,90]. There are some calls to adopt standardized AMR data presented in published papers, wishing to make the ndings interpretable and comparable from the perspective of scarce homogeneity [111].…”
Section: Discussionsupporting
confidence: 79%
“…In China, the overall carbapenem-resistant Enterobacteriaceae infection incidence per 10 000 discharges was 4.0 and varies signi cantly by region [85]. However, no carbapenem-resistant Enterobacteriaceae was found in a recent systematic review from Cambodia [86]. Carbapenemases have a global distribution, but substantial variability exists at the regional and continental levels.…”
Section: Discussionmentioning
confidence: 99%
“…This result was expected since FQ is one of the most commonly used antibiotics in non-TB infections in Cambodia and the drug is accessible without prescription at the counter of pharmacies. 39 High incidence of FQ-resistance has also been reported in many parts of the world, particularly in countries with a high TB burden. 40 FQ is used in both the standardized and shorter MDR-TB regimen and is considered as an essential part of the MDR-TB regimen.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of 24 studies published between 2000 and 2018 reported resistance rates for selected pathogens in Cambodia (118). The median resistance rates, calculated by combining all specimens, were reported in this study.…”
Section: Cambodiamentioning
confidence: 90%